Parental Roles in "The Circle of Life" Representations of Parents and Parenting in Disney Animated Films from 1937 to 2017. Issue 1 (2nd January 2020) - Zurcher, Jessica D.; Brubaker, Pamela Jo; Webb, Sarah M.; Robinson, Tom
Abstract : With such an expansive global reach, greater research is needed to evaluate messaging within Disney animated films as it relates to societal implications. The present analysis examined the portrayal of parents and parenting over time through a census content analysis of 85 Disney animated and computer-animated films that aired from 1937 to 2017. The constructs of parent demographics, parental configurations, parent roles within and outside of the home, and parenting behaviors were examined. Results revealed that the vast majority of parents were viewed as mature, competent adults, with 56% use of the authoritative parenting style. Father figures were significantly more likely to use authoritarian and permissive parental approaches whereas female caregivers were more authoritative. Although parents were portrayed as overall mature and competent adults, implications are discussed regarding the portrayal of parental approaches that do not provide children with the support needed to overcome obstacles.